Brain-wide map of efferent projections from rat barrel cortex - Zakiewicz, Izabela M.; Bjaalie, Jan G.; Leergaard, Trygve B. (Frontiers in Neuroinformatics, 2014)
The somatotopically organized whisker barrel field of the rat primary somatosensory (S1) cortex is a commonly used model system for anatomical and physiological investigations of sensory processing. The neural connections of the barrel cortex have been extensively mapped. But most investigations have focused on connections to limited regions of the brain, and overviews in the literature of the connections across the brain thus build on a range of material from different laboratories, presented in numerous publications. Furthermore, given the limitations of the conventional journal article format, analyses and interpretations are hampered by lack of access to the underlying experimental data. New opportunities for analyses have emerged with the recent release of an online resource of experimental data consisting of collections of high-resolution images from 6 experiments in which anterograde tracers were injected in S1 whisker or forelimb representations. Building on this material, we have conducted a detailed analysis of the brain wide distribution of the efferent projections of the rat barrel cortex. We compare our findings with the available literature and reports accumulated in the Brain Architecture Management System (BAMS2) database. We report well-known and less known intracortical and subcortical projections of the barrel cortex, as well as distinct differences between S1 whisker and forelimb related projections. Our results correspond well with recently published overviews, but provide additional information about relative differences among S1 projection targets. Our approach demonstrates how collections of shared experimental image data are suitable for brain-wide analysis and interpretation of connectivity mapping data.